Sustainable Heritage Development: Learning from Urban Conservation of Heritage Projects in Non Western Contexts - Elnokaly, Amira; Elseragy, Ahmed (European Journal of Sustainable Development, 2013)
Urban conservation has been a subject of academic and professional discourse for over three decades. Conservation in this paper is seen as an umbrella term that covers a wide spectrum of issues that can be classified under three categories: socio-physical, socio-cultural, and environmental concerns. It is also manifested as a process of evolutionary development which involves preserving, restoring, adapting old structures, while introducing new ones; a process that respects the continuity of history and tradition, the needs of inhabitants and their cultural aspirations. This understanding indicates that urban conservation is a process of continuous yet controlled interventions in the environment. The extent and the degree of such an intervention is dependent upon crucial factors that include the value system adopted by the society, the resources available, and the cultural and environmental context within which such an intervention takes place. With an ultimate goal to discern lessons from urban conservation practices, urban rehabilitation and adaptive re-use is discussed with reference to a number of non-western case studies. The paper aims at exploring the merits of six conservation and rehabilitation projects which have received considerable coverage and recognition on a national and international level while they have not been put into contextual comparison with others. Merits of these projects are analysed and highlighted in this article to work as an archetype for similar projects around the world. The paper concludes that to maintain sustainability of the revitalisation and urban conservation approaches, the typical urban tissue and essential qualities of the historic areas and of the life of the communities residing there should be maintained, while adapting the physical structures and activities to some of the today’s requirements.